Sonic Histories of Occupation Experiencing Sound and Empire in a Global Context - Taylor, Jeremy E.; Skelchy, Russel (Bloomsbury Academic, 2022)
A transdisciplinary and comparative exploration into how foreign occupation and imperialism have shaped auditory environments, and how occupied peoples have responded to such conditions